Menggali Makna Toleransi Antar Umat Beragama dalam Kerangka Keselarasan Sosial: Exploring the Meaning of Interfaith Tolerance within the Framework of Social Harmony - Wulandari, Sekar Kirana; Yasmin, Andien Rizkyas; Sugiarti, Nadila Putri Budi; Komariah, Siti; Hyangsewu, Pandu (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
Indonesia, with its extensive diversity in religions, races, cultures, and ethnic groups, confronts the dual potential of this diversity: as both a source of harmony and a source of conflict. This study utilizes an explanatory sequential mixed-methods approach to explore the comprehension and practice of interfaith tolerance among university students and to identify strategies for enhancing social harmony. By employing questionnaires and conducting interviews with students from varied religious backgrounds, the research reveals that although there is an overarching understanding of tolerance, its actual implementation is frequently hindered by religious fanaticism and other social barriers. The findings emphasize that education, particularly at the tertiary level, plays a pivotal role in cultivating an effective understanding and enactment of tolerance. Consequently, the study advocates for the enhancement of curricula by integrating Pancasila values and multicultural education to fortify tolerance and mitigate fanaticism. This research underscores the significance of interfaith dialogue and education in promoting social harmony and inclusive national development in Indonesia. Abstrak Indonesia, sebagai negara yang kaya akan keanekaragaman agama, ras, budaya, dan etnis, menghadapi potensi dualistik keberagaman ini: sebagai sumber harmoni dan juga sebagai sumber konflik. Penelitian ini menggunakan metode campuran sekuensial eksplanatori untuk memahami pemahaman dan praktik toleransi antar umat beragama di kalangan mahasiswa, serta mengidentifikasi strategi untuk meningkatkan harmoni sosial. Melalui kuesioner dan wawancara dengan mahasiswa dari berbagai latar belakang agama, penelitian ini mengungkap bahwa meskipun ada pemahaman tentang toleransi, praktiknya sering terhambat oleh fanatisme agama dan penghambat sosial lainnya. Hasil menunjukkan bahwa pendidikan, khususnya di perguruan tinggi, memegang peran kunci dalam membentuk pemahaman dan praktek toleransi yang efektif. Implikasinya, peningkatan kurikulum yang mengintegrasikan nilai-nilai Pancasila dan pendidikan multikultural diperlukan untuk memperkuat toleransi dan mengatasi fanatisme. Penelitian ini menekankan pentingnya dialog antaragama dan pendidikan dalam mempromosikan keselarasan sosial dan pembangunan nasional yang inklusif di Indonesia.